Bioactive cytochalasans from the desert soil-derived fungus Chaetomium madrasense 375 obtained via a chemical engineering strategy - Guo, Qingfeng; Shen, Shenyu; Wang, Xinyang; Shi, Lei; Ren, Yuwei; Li, Dandan; Yin, Zhenhua; Zhang, Juanjuan; Yang, Baocheng; Wang, Xuewei; Ding, Gang; Chen, Lin (Frontiers in Microbiology, 2024)
The chemical engineering of natural extracts has emerged as an effective strategy to produce diverse libraries of chemicals, making it integral to drug discovery. A chemically engineered strategy based on the epoxidation and ring-opening reactions was used to prepare the diversity-enhanced extracts of Chaetomium madrasense 375. Eleven unnatural cytochalasan derivatives (1-11) with unique functional groups such as amine and isoxazole were isolated and characterized from these chemically engineered extracts of C. madrasense 375. The identification of these new structures was accomplished through comprehensive spectroscopic analysis, supplemented by synthetic considerations. Notably, compounds 5 and 13-16 displayed potent phytotoxic effects on Arabidopsis thaliana, while compounds 1, 2, 5, 10, and 12 demonstrated inhibitory activities on LPS-induced NO production in RAW264.7 cells. Among them, compound 1 could inhibit the upregulated expression of the inducible nitric oxide synthase (iNOS) protein induced by LPS, while also decreasing the production of pro-inflammatory cytokines (IL-6) and influencing the phosphorylation of p38, ERK1/2, and JNK at 100 μM, respectively. Our studies demonstrate that the chemically engineered strategy of natural product extracts should be an efficient technique for the generation of novel bioactive molecules.